In situ ferromagnetic resonance capability on a polarized neutron reflectometry beamline. Issue 1 (26th January 2018) - Kostylev, Mikhail; Causer, Grace L.; Lambert, Charles-Henri; Schefer, Thomas; Weiss, Charles; Callori, Sara J.; Salahuddin, Sayeef; Wang, Xiaolin L.; Klose, Frank
Abstract : The design of a polarized neutron reflectometry sample environment capable of simultaneously measuring the ferromagnetic resonance response of a magnetic thin film is presented. Abstract : This article describes a novel approach which allows for the mutual determination of a ferromagnetic thin film's static and dynamic magnetic behaviours in the presence of an external thermodynamic stimulus. Using a combination of polarized neutron reflectometry (PNR) and ferromagnetic resonance (FMR) techniques, it is shown that information such as magnetic depth profiles and magnetization dynamics can be obtained for a ferromagnetic film in both transient and static states in the presence of a hydrogen gas atmosphere. Presented here are the proposed scheme, the instrumentation concept and the first experimental results obtained from implementing a custom‐made PNR with an in situ FMR sample chamber on the PLATYPUS time‐of‐flight reflectometer beamline at the Australian Centre for Neutron Scattering (ANSTO).